How does the presidential election period affect the performance of the state-owned enterprise in Indonesia? - Iman Harymawan; Mohammad Nasih; Novrys Suhardianto; Elvia R. Shauki (Cogent Business & Management, 2020)
This study investigates the differences between the SOEs and non-SOEs financial performance and how the presidential election affects their performance. This study uses 3,716 firm-year observations for firms listed on the Indonesian Stock Exchange from 2001 to 2014 as the final sample and uses regression to test the hypotheses. In Indonesia, on average, about 25 parties involved in the presidential election in the past three elections. Due to the complexity of the data collection, this study omits the effect of the unique political parties that also could affect the performance of SOE. This study finds that SOEs outperform financial performance of non-SOEs over the sample periods. Interestingly, this study also finds that the excellent financial performance of SOEs disappears around the election period. It indicates that being a board member of state-owned enterprises (SOEs) is a political position rather than a professional position. For policymakers, these results indicate that election periods influence (reduce) the financial performance of SOEs in Indonesia. This study enhances our understanding of how presidential elections affect the performance of SOEs in Indonesia.
Keywords: D72; G30; L25; 650; election; firm performance; political connections; state-owned enterprises